Circumscribed cicatricial alopecia due to localized sarcoidal granulomas and single‐organ granulomatous arteritis: a case report and systematic review of sarcoidal vasculitis. (4th June 2015) - Yazdani Abyaneh, Mohammad‐Ali; Raghu, Preethi; Kircher, Kenneth; Kutzner, Heinz; Alison, Kortz; Carlson, John Andrew
Abstract : Vasculitis associated with sarcoid granulomas is an uncommon phenomenon. A 72‐year‐old female presented with an expanding region of circumscribed alopecia and scalp atrophy of 2 months duration. Biopsy showed non‐caseating granulomas, dermal thinning, loss of follicles, fibrosis and muscular vessels disrupted by mixed lymphocyte, macrophage and giant‐cell infiltrates. Affected vessels had loss and fragmentation of the elastic lamina, fibrous replacement of their walls and luminal stenosis (endarteritis obliterans). Dermal and vascular advential intralymphatic granulomas and lymphangiectases were found by D2‐40 expression, suggesting lymphatic obstruction and poor antigen clearance. No evidence of a post‐zoster eruption, systemic sarcoidosis or systemic giant‐cell arteritis was found. Two years later, prednisone had halted – but not reversed – progression of her alopecia. Review of the literature showed two types of vasculitis associated with sarcoid granulomas: (i) acute, self‐limited leukocytoclastic vasculitis and (ii) chronic granulomatous vasculitis (GV). Persistence of non‐degradable material or antigen contributes to the pathogenesis of granulomatous inflammation. In this case, lymphatic obstruction probably impeded clearance of nonimmunologic and/or immunologic stimuli permitting and sustaining the development of sarcoid granulomas and sarcoid GV, ultimately causing scarring alopecia and cutaneous atrophy.